STRATEGI MANAJEMEN PRODUKSI PROGRAM BERITA DETAK MELAYU DI RIAU TELEVISI - Mellisa Louhenapessy Cindy Kharisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
One of the programs that are a mainstay of television stations in Indonesia is a news program. Competent public television station captured the audience by presenting a news program that is certainly packaged and presented as attractive as possible is no exception Detak Melayu news program. Intense competition in the packaging of this news, making Detak Melayu strive to improve the quality of reporting in order to remain able to attract an audience of spectators. For this reason this study aims to see how management strategies include strategic planning, organizing strategies, mobilization strategy and control strategies in the production of news programs Detak Melayu in Riau Televisi.This study used a qualitative method with descriptive approach. The object of research is the news program production management strategies Detak Melayu which produced by RiauTelevisi. Subjects consisted of four ranks of Riau Televisi and five journalists, were determined by purposive method. Data collection techniques used are observation, interview, and documentation.Results from this study describes how the application of planning, organizing, actuating, and controlling (POAC) in the news program production management strategy as an attempt to Detak Melayu produce a quality news product. (1) Detak Melayu applies four phase which carried out in three forms, namely, the planning meeting news topics, placement planning meetings reporter and cameraman, and projections as well as an evaluation meeting. (2) The second phase is organization, Detak Melayu have determined the distribution of each reporter and cameraman in accordance with the coverage of each “base camp”to work description assigned. Furthermore, (3) the third phase is actuating began from news coverage, shooting, script writing news, post-production and dubbing script that consists of news, news editing process, manufacture rundown of news and news programs aired Detak Melayu.(4) And the fourth is controlling which is conducted Detak Melayu one of them is the projection and evaluation meetings. The entire series of the process is a form of strategy management in the production process to improve the quality news in Detak Melayu program.Keyword: Strategy, Management, Production Management Strategy Television,Television, and News